JANUARY EFFECT DALAM RETURN DAN VOLATILITAS PERDAGANGAN SAHAM SERTA KONDISINYA SAAT COVID-19 - Agustian, Sulistyana Dwi; Satria, Dias (Journal of Development Economic and Social Studies, 2023)
This final research was conducted to identify the existence of the January effect phenomenon in Indonesia’s banking sector from 2018 to 2022 by analyzing stocks data of BCA, BNI, BRI, BTN and Bank Mandiri as research samples using the Rstudio program as a tool in hypothesis testing the independent sample t-test as a parametric test as well as the Wilcoxon rank sum test as a non-parametric test. The conclusion of this study showed that in the LQ-45 banking sector there were symptoms of the January effect in 2018, 2019 and 2021.